The Role of Childhood Trauma in Marital Conflict: A Study on Wives - Lahdji, Mona; Sahrani, Riana; Suyasa, P. Tommy Y. S. (Biopsikososial: Jurnal Ilmiah Psikologi Fakultas Psikologi Universitas Mercubuana Jakarta, 2025)
This study explores the role of childhood trauma in marital conflict among wives in Indonesia. Childhood trauma refers to negative experiences caused by physical or psychological abuse, neglect, or sexual assault. The primary objective of this study was to investigate how childhood trauma can predict marital conflict within households. A quantitative correlational design was used, involving 203 wives who had been married for at least one year, aged between 21 and 63 years. Data were collected using the Childhood Trauma Questionnaire and the Marital Conflict Questionnaire. Spearman’s rho correlation analysis revealed a significant positive relationship between childhood trauma and marital conflict. The more individuals experience childhood trauma, the higher the level of marital conflict. Significant correlations were found between childhood trauma and marital conflict frequency, conflict impact, and emotional impact, with emotional abuse being the strongest predictor. The findings also show that emotional abuse in childhood is the strongest predictor of emotional impact during marital conflicts. Therefore, this study emphasizes the importance of considering childhood trauma in understanding marital dynamics and its impact on conflict.